Education and democracy - Hoyos, Luis Eduardo (Estudios de Filosofía, 2010)
In the paper it is presented a conceptual defense of a liberal and democratic conception of education. Since the main function of individual’s education consists in his socialization and the existence of educated individuals is the minimal guarantee for a social creative and enriched process, then the development of democracy is internally bounded with the development of education in general and of civic education in particular. Therefore the politician, in a democratic system, should be a pedagogue. The reflection, principally conceptual, ends with the presentation of an example of the recent political history of Colombia.